Determinants of prenatal breastfeeding knowledge, attitudes and self-efficacy among Burmese migrant pregnant mothers in Samut Sakhon Province, Thailand: a cross-sectional study - Montakarn Chuemchit; Zayar Lynn (BMJ Open)
Objective The study aimed to explore the determinants of prenatal breastfeeding knowledge, attitudes and self-efficacy among Burmese migrant pregnant mothers in Samut Sakhon Province, Thailand.Design The data were collected as part of a baseline survey of a randomised controlled trial.Setting and participants A total of 198 Burmese migrant mothers between 28th and 34th weeks of gestation were recruited from the antenatal care clinic of Samut Sakhon Hospital.Primary outcome measures Breastfeeding knowledge, attitudes and self-efficacyResults The prevalence of good breastfeeding knowledge was 65.7% (n=130), positive attitudes towards breast feeding were 55.1% (n=109) and high breastfeeding self-efficacy was 70.7% (n=140). Multivariate logistic regression models revealed that mothers aged above 25 years (adjusted OR, AOR 3.1, 95% CI 1.2 to 7.9), being Bamar (AOR 2.3, 95% CI 1.2 to 4.4), having support from husband (AOR 2.3, 95% CI 1.2 to 4.6) and having previous childbirth experience (AOR 2.5, 95% CI 1.3 to 4.8) were the main determinants of good breastfeeding knowledge. Similarly, being Bamar (AOR 2.8, 95% CI 1.5 to 5.3), having high school education (AOR 4.3, 95% CI 1.8 to 10.1) and having access to workplace breastfeeding support (AOR 5.3, 95% CI 1.4 to 20.1) were found to be significant predictors of positive attitudes towards breast feeding. Moreover, mothers aged above 25 years (AOR 2.9, 95% CI 1.1 to 7.8), being Bamar (AOR 2.4, 95% CI 1.2 to 5.1), being unemployed (AOR 7.8, 95% CI 1.9 to 31.9), having support of husband (AOR 3.2, 95% CI 1.5 to 7.0), having previous breastfeeding experience for 6 months or more (AOR 5.0, 95% CI 2.1 to 11.7) and having intention to exclusively breastfeed (AOR 2.7, 95% CI 1.3 to 5.8) had significant associations with high breastfeeding self-efficacy.Conclusion The prenatal breastfeeding knowledge, attitudes and self-efficacy among Burmese migrant mothers were influenced by many factors. A comprehensive understanding of these factors will enable policy-makers and healthcare providers to develop context-specific interventions for the promotion of exclusive breast feeding among Burmese migrant mothers in Thailand.Trial registration number TCTR20230310004.